The Structure and Limits of Criminal Law - Barton, Joshua Samuel (2014)
The book The Structure and Limits of Criminal Law (Ashgate) collects and reprints classic articles on three topics: the conceptual structure of criminal law doctrine, the conduct necessary and that sufficient for criminal liability, and the offender culpability and blameworthiness necessary and that sufficient for criminal liability. The collection includes articles by H.L.A. Hart, Sanford Kadish, George Fletcher, Herbert Packer, Norval Morris, Gordon Hawkins, Andrew von Hirsch, Bernard Harcourt, Richard Wasserstrom, Andrew Simester, John Darley, Kent Greenawalt, and Paul Robinson. This essay serves as an introduction to the collection, explaining how each article fits into the larger debate and giving a brief summary of each that will orient the (primarily student) reader. Part I considers how best to construct a conceptual framework for criminal law. Under existing law, criminal law doctrine tends to operate in one of three ways: defining an offense, or defining a general defense that operates independent of the offense requirements to bar liability, or defining a doctrine of imputation that treats the actor as if he satisfies an offense requirement that he does not in fact satisfy. However, one could organize criminal law doctrines differently, around the different function that each performs: articulating ex ante the rules of conduct or adjudicating ex post the violation of those rules of conduct, to assess liability and the grade of the liability. Part II examines the debate over what conduct should be necessary for criminal liability, and what conduct should be sufficient. Harm to another is surely necessary but probably insufficient. And the harm principle has been stretched so far that it cannot now, by itself, serve as a meaningful limitation in the modern criminalization debate. On the other hand, immorality or at least condemnability of conduct is surely insufficient but probably necessary: on both philosophical and empirical grounds, there is reason to think that conduct should not be criminalized unless society regards it as morally blameworthy. Part III considers the debate over what offender culpability and blameworthiness should be necessary for criminal liability, and what should be sufficient. Despite calls by some to ignore blameworthiness in the name of prevention, the increasingly more accepted view is that criminal liability should be imposed only on the blameworthy. Indeed, many go further, arguing that also the extent of the offender's liability and punishment should depend upon the extent of his blameworthiness. This means retaining the mens rea requirement, offering a full array of excuse defenses, and, in its strongest form, adopting desert as an inviolable distributive principle